2018
DOI: 10.1109/tpwrs.2017.2732443
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Voltage Sensitivity Approach for the Decentralized Control of DG Plants

Abstract: Abstract-Renewable distributed generation (DG) is likely to be actively controlled in future distribution networks to mitigate voltage issues resulting from high penetrations. This requires understanding the corresponding dependencies between voltage magnitudes and DG active/reactive power outputs. One approach to compute these dependencies is to use classical sensitivity methods such as those based on the Jacobian matrix inverse. However, updating the latter involves extensive remote monitoring. This paper pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…S VQ t,ij ∂V t,i /∂Q t,j denotes voltage-to-reactive-power sensitivity between V t,i and Q t,j . P t,j and Q t,j represent active and reactive power injection at node j in time period t. Specifically, S VP t,ij and S VQ t,ij are calculated for every time period using real-time local measurements of the deviation of nodal voltage magnitude to unit changes in nodal active or reactive power output [27]. Alternatively, if there are µPMUs in the system, the sensitivities can also be estimated via network equivalents with µPMU measurements [17].…”
Section: Model Of Intra-area Voltage Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…S VQ t,ij ∂V t,i /∂Q t,j denotes voltage-to-reactive-power sensitivity between V t,i and Q t,j . P t,j and Q t,j represent active and reactive power injection at node j in time period t. Specifically, S VP t,ij and S VQ t,ij are calculated for every time period using real-time local measurements of the deviation of nodal voltage magnitude to unit changes in nodal active or reactive power output [27]. Alternatively, if there are µPMUs in the system, the sensitivities can also be estimated via network equivalents with µPMU measurements [17].…”
Section: Model Of Intra-area Voltage Controlmentioning
confidence: 99%
“…Thus, we choose the end node of the boundary branch as the boundary node of the two neighboring sub-areas in the inter-area coordination. For the boundary node i between sub-area a and b, the local information of the SOP in sub-area b for interacting to sub-area a through boundary node i is calculated according to (27) and (28):…”
Section: Boundary Information For Interactionmentioning
confidence: 99%
“…(2) However, the above method requires real-time information on all buses of the distribution system to be considered for its time-varying operating conditions. Hence, numerous measurements and communication infrastructures are necessary, but the requirements are highly expensive [23,24]. To obtain voltage sensitivity under the limited measurements, this study proposes a system reduction as shown in Figure 7.…”
Section: Control Gain Based On Jacobian Matrixmentioning
confidence: 99%
“…Ja is the Jacobian matrix in the Newton-Raphson method [29,30] and the derivatives of voltage can be derived by the Jacobian matrix Ja from (5). The derivatives of the voltage amplitude and phase angle can be written as:…”
Section: The Power Sensitivity Applicationmentioning
confidence: 99%